India Talking: Politics, Democracy and News Television - Mehta, Nalin (Television in India: Satellites, Politics and Cultural Change, 2008)
After four decades of state monopoly over television Indian viewers gottheir first taste of private television in the early 1990s. By 1998, the first of India’s private 24-hour news channels was on the airwaves and by 2007more than 300 satellite channels were broadcasting into Indian homes. Ofthese, 106 broadcast news in 14 languages and as many as 54 of these were24-hour news channels in 11 languages.1 These are conservative figures thatdo not include many foreign and local cable networks that also broadcastnews.2 Even so, the numbers are a stark illustration of how the Indian statelost control over television broadcasting despite its best efforts to the con-trary. No other country in the world has such a concentration of private news channels as India. The creation of a television public has significantimplications for democracy and this essay focuses on what 24-hour newsmeans for India. It argues that the emergence of television news networkshas greatly enhanced and strengthened deliberative Indian democracy.Commercial mass media stands at the junction of politics and the economy,enabling the entry of citizens onto the stage of politics, while simultaneouslyseeking to appropriate that energy for its own commercial benefit (Rajago-pal, 1999: 133). This is a claim that needs to be differentiated from the usual journalistic self-image of the fourth estate acting as vigilant defenders ofdemocratic ideals. That notion should not be romanticised too muchbecause news production itself is a cultural process that cannot be separatedfrom its social environment. News producers always function under certaininstitutional constraints that are endemic to the news-gathering process.Leftist and liberal scholars of the media differ in their emphasis but allagree that news production is always circumscribed by institutional filters.3News is ‘more a pawn of shared suppositions than the purveyor of selfconscious messages’ (Schudson, 1995: 15). Yet, the media are important,and while it is difficult to draw direct causal linkages, there is no doubt thatthey initiate and create a new sphere of political action.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Inde (corpus analysé); Singapour (lieu de production du savoir); _Nettoyé

‘Shanghai is burning’: Extravaganza, Transgender Representation and Transnational Cinema - Bao, Hongwei (Global Media and China, 2018)
This article offers a critical analysis of Matthew Baren’s 2018 film Extravaganza, a documentary about drag scenes in Shanghai. By focusing on some drag performers represented in this film, in tandem with an examination of the social and industry contexts of the film, as well as my interviews with the filmmaker and performers, I problematise the gender identity of the performers and the national identity of the film. Drawing on Deleuze and Guattari’s notion of ‘becoming’ and Song Hwee Lim’s discussion of ‘trans’, I propose to think about certain modes of transnational production with the critical concept of ‘becoming trans’. ‘Becoming trans’ offers a productive way of conceptualising new modes of ‘minor’ transnational cinematic connections in a globalised world without having to resort to identity politics.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

New Queer Sinophone Cinema: Local Histories, Transnational Connections - Pecic, Zoran 1981- (Palgrave pivot, 2016)
This book looks closely at some of the most significant films within the field of queer Sinophone cinema. Examining queerness in films produced in the PRC, Taiwan and Hong Kong, the book merges the Sinophone with the queer, theorising both concepts as local and global, homebound as well as diasporic.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé